Strategi Sekolah Dalam Menyukseskan Penerimaan Peserta Didik Baru (Studi Kasus di SD Muhammadiyah 1 Ngaglik): Studi Kasus di SD Muhammadiyah 1 Ngaglik - Ramadhan, Andriawan Fajar; Maryani, Ika (Universitas Kristen Satya Wacana, 2024)
Competition for new student admissions in schools across Indonesia has recently become a topic of considerable interest. A school's strategy in implementing the New Student Admission Program (PPDB) is one of the key factors determining the success of its marketing efforts. In reality, inadequate PPDB strategies often prove detrimental to some schools. SD Muhammadiyah 1 Ngaglik is one example of an elementary school that has successfully executed its PPDB with the right strategy. The purpose of this study is to describe and analyze the PPDB strategy at SD Muhammadiyah 1 Ngaglik. This research employs a qualitative approach with a descriptive design. The study was conducted at SD Muhammadiyah 1 Ngaglik during the 2024 PPDB period. The research data sources include the school principal, the PPDB coordinator, three PPDB committee members, and three parents of new students. Data collection techniques involve interviews, observations, and documentation using interview guidelines, observation guides, and documentation checklists. The triangulation method applied includes data source triangulation reinforced by technique triangulation. The findings of this study reveal that: 1) The PPDB strategy at SD Muhammadiyah 1 Ngaglik begins with the planning stage, which includes environmental analysis, collaboration planning, determining the PPDB committee, and planning for printed and digital promotions as well as funding, 2) The implementation stage involves signing Memorandums of Understanding (MoUs) with kindergartens, organizing supporting activities, and promoting the program through print and digital media, 3) Monitoring the implementation of PPDB is carried out through regular meetings to discuss achievements, challenges, and solutions, 4) Evaluation is conducted to assess the success of the PPDB, including evaluation meetings, planning for the next year's PPDB, and follow-up actions.